PEMIKIRAN ABU YUSUF DAN RELEVANSINYA DENGAN STRATEGI PEMULIHAN EKONOMI INDONESIA PASCA-PANDEMI - Anisa, Lina Nur (Fakultas Ekonomi Bisnis Islam, 2023)
This article aims to discuss Abu Yusuf's thoughts and their relevance to Indonesia's post-pandemic economic recovery strategy. This article research uses a qualitative approach with the type of library research. The data collection technique used is documentation, with data analysis techniques in the form of content analysis, induction and deduction. The conclusion from the discussion of this article is as follows. Abu Yusuf's thinking, which emphasizes economic justice, the active role of the state, and fair management and redistribution of wealth, is very relevant to the modern economic context, especially in Indonesia, especially in facing economic challenges exacerbated by the COVID-19 pandemic. The study of how these principles can be integrated into contemporary economic systems provides important insights for the development of a more inclusive and sustainable economy. Policymakers should consider a more systematic and coordinated integration of zakat to support social programs and economic development, especially in supporting community groups most affected by the pandemic. It is necessary to implement a fairer and more proportional taxation system, based on the principles of economic justice taught by Abu Yusuf, to ensure a more equal and effective distribution of the tax burden. The state must take a more active role in regulating and supporting critical economic sectors, ensuring that the economic policies implemented can stimulate growth while preventing wider inequality.